Theological Education in Modern Society - Vorozhtsov, Vladimir (Bogoslovskie razmyšlenija, 2007)
The church and society are two opposite values, trying mutually to influence one another. In the development of church and society the law of "challenge answer" is valid. Spiritual education is an instrument, which allows the church to give an adequate answer to the challenge of the society and current times. This paper is about the particularities and challenges of the theological education in Russia. At the same time the subject under discussion in the article is relevant worldwide.